Boar spermatozoa cryopreservation (Maxi-straws method) - Tirapicos Nunes J.; Charneca R.; Milhano A.; Almeida J.A. (Tradition and innovation in Mediterranean pig production, 2000)
Artificial insemination (AI) using frozen semen, still possesses some limitations. Fertility and prolificacy rates are quite low when frozen semen is used, compared with fresh semen. However, some progress has been achieved by using improved new technologies. One of such techniques is the freezing of semen by using the method proposed by Westendorf et al. (1975). Our trial is also based on Westendorf et al. (1975) method, tested the efficacity of freezing semen, assessing it in vitro, after thawing and dilution into 4 different solutions. These were the SD - glucose sodium citrate solution (37 g of glucose; 1.25 g of sodium bicarbonate; 6 g of sodium citrate; 1.25 g of EDTA; 0.75 g of potassium chloride and 1000 ml of distilled water); the BTS Beltsville thawing solution; the MR-A - Commercial extender for fresh semen and the ACROMAX - Commercial extender for fresh semen. Semen in vitro evaluations took place at the 10th and 20th day after preservation into liquid nitrogen.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)